Measuring the filtration efficiency of the Continuous Plankton Recorder - A Walne; Graeme Hays; P Adams (1998)
The Continuous Plankton Recorder (CPR) survey has analysed over 160 000 plankton samples taken in the North East Atlantic over the last 60 years. However, flowmeters have not been routinely fitted to the recorders and there has been the implicit assumption that a CPR sample represents the organisms filtered from 3 m3 of sea water. We describe an electromagnetic flowmeter designed for the CPR and present results which show that on occasions the filtered volume per sample varied significantly from this value.